EU´s image among Icelandic voters and the importance of its membership´s issues - Eysteinsson, Friðrik; Diego, Dagbjört Ágústa H.; Kristinsson, Kári (Stjórnsýslustofnun, 2013)
Icelanders applied for EU membership in 2009, but in 2013 when the new government took office, negotiations were put on hold. The question whether Iceland should join the EU or not has been a source of debate among Icelanders for many years. This paper´s authors therefore found it interesting to study EU´s image based on whether voters are in favor or not of joining it or which political party they vote for and how important the main issues of the debate are to them. A quantitative research in the form of a questionnaire was used for this purpose. The population of interest was voters in Iceland. A convenience sample consisting of students at the University of Iceland, friends of the authors on Facebook and others was used. EU´s image among those who are in favour of EU membership or vote for political parties that are in favour of joining it is better when it comes to image factors which could be considered positive. EU´s image among those who are not in favour of EU membership or vote for political parties that are not in favour of joining it is better when it comes to image factors which could be considered negative. The issues that those who are in favour of EU membership emphasize in the debate are more important to the voters who are in favour of joining the EU whereas the issues that are emphasized by those who are against EU membership are more important to those who are against joining the EU. Íslendingar sóttu um aðild að ESB árið 2009 en gert var hlé á viðræðum um umsókn árið 2013 þegar ný ríkisstjórn tók við völdum. ESB og möguleg aðild að sambandinu hefur verið bitbein hjá þjóðinni í fjölmörg ár. Í því ljósi þótti höfundum áhugavert að skoða hver væri munurinn á ímynd sambandsins eftir afstöðu kjósenda til inngöngu í það og / eða eftir því hvaða stjórnmálaflokk þeir kjósa og hversu miklu máli áhersluþættir umræðunnar um aðild skipta þá. Gerð var megindleg rannsókn í formi spurningakönnunar. Þýðið var kosningabært fólk á Íslandi. Notast var við hentugleikaúrtak meðal nemenda Háskóla Íslands, vina á ...